Pengaruh Story Reading (Buku Bilingual) terhadap Perkembangan Kecerdasan Linguistik Anak Usia Dini - Azhara , Nur; Hayani, Nur (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Linguistic intelligence is the ability to organize thoughts clearly and be able to use them competently through words to express thoughts in speaking, reading and writing. This study aims to find out the effect of story-reading on the development of linguistic intelligence in early childhood, especially in Ra Al-WasliyahJl. Asahan Km. 17 woke up. This research was conducted at RA Al - Wasliyah jl. Asahan km. 17 Wake up. On March 6 - March 8, 2023. This research uses the type of Classroom Action Research (Teacher PTK) which is research conducted in the classroom using an action to improve the quality of the teaching and learning process in order to obtain better results than before. From the results of the study it was found that story-reading had several positive influences on increasing linguistic intelligence, namely: (1) early childhood knew and understood new vocabulary (2) understood the plot of a story (3) arranged words to convey the implied message of a story. In conclusion, that storyreading can have an influence on the development of linguistic intelligence in early childhood.